Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Help me to solve the following Partial differential equation:

$$\frac{\partial u}{\partial t}+u\frac{\partial u}{\partial x}=-ku, \;\;u(x,0)=2, \;\; k>0 \;\text{is a constant}\;\; \text{and} \;\; x \;\text{is real}$$ Thanks!

share|cite|improve this question

Let $\gamma_y(t)$ be the curve that solves the ordinary differential equation $$ \frac{\mathrm{d}}{\mathrm{d}t}\gamma_y(t) = u(t,\gamma_y(t)) $$ with initial condition $$ \gamma_y(0) = y$$

We have that $$ \frac{\mathrm{d}}{\mathrm{d}t} u(t,\gamma_y(t)) = \frac{\partial}{\partial t} u(t,\gamma_y(t)) + u(t,\gamma_y(t)) \frac{\partial}{\partial x} u(t,\gamma_y(t)) = -k u(t,\gamma_y(t)) $$ from the equation. So this means that

$$ u(t,\gamma_y(t)) = u(0,\gamma_y(0)) e^{-k t} $$

Plug this back into the equation for $\gamma$ we have

$$ \frac{\mathrm{d}}{\mathrm{d}t} \gamma_y(t) = u(0,\gamma_y(0)) e^{-kt} = u(0,y) e^{-k t} $$

so that

$$ \gamma_y(t) = \gamma_y(0) - \frac{1}{k} u(0,y) e^{-k t} = y - \frac{1}{k} u(0,y) e^{-k t}$$

So given a point $(t,x)$ we first solve for $y$ using the equation $$ x = y - \frac{1}{k} u(0,y) e^{-k t} $$ then we apply the equation that $$ u(t,x) = u(t,\gamma_y(t)) = u(0,y) e^{-k t} $$

For our specific case, using that $u(0,y) = 2$ by assumption, we have that $$ x = y - \frac{2}{k} e^{-kt}$$ or that $$ y = x + \frac{2}{k} e^{-kt}$$

Then we have that $$ u(t,x) = u(t,\gamma_y(t)) = u(0,y)e^{-kt} = 2 e^{-kt} $$

Remark: note that by the symmetry of the equation, given that the initial data does not depend on $x$, the solution also does not depend on $x$. So your PDE actually can be reduced to the ODE $\frac{\mathrm{d}}{\mathrm{d}t} u = - k u$ and the solution read off accordingly. But since you mentioned "method of characteristics" in the question title, I showed you how to solve the problem for any initial condition using said method.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.